(untitled) (Intent Research Scientific Journal, 2025)
The article deals with the socio-economic situation of Karakalpakstan in 1925-1930. The results of the social policy of the Soviet power in Karakalpakstan in 1925-1930s, the transition to collectivization of agriculture in the conditions of Karakalpakstan are analyzed. Actual issues of formation of socio-political climate among dehkanstvo, demographic situation, natural and geographical features of the national economy, which in the historical and comparative analysis gives the opportunity to highlight a number of trends and factors that determine the practical significance of the study in the modern historical period.